ANALISIS KESELAMATAN DAN KESEHATAN KERJA (K3) MENGGUNAKAN METODE HIRARC PADA SUBAK DELOD SEMA - Arya, Moch Arya Puanggawa Amir TK; I Made Dwi Budiana Penindra; Ni Luh Putu Lilis Sinta Setiawati; Dr. Ir. I Gusti Ngurah Priambadi, MT; Mia Juliana, S.TP., M.T; Ni Made Cyntia Utami, S.T., M.T (JURNAL RISET DAN APLIKASI TEKNIK INDUSTRI, 2023)
Subak is one of Bali's local wisdoms related to rice field irrigation systems. The subak studied on this occasion was the Delod Sema subak located in Bali. In Subak Delod Sema there are several stages of the work process that have the potential for minor or serious accidents to occur. Lack of understanding of the concept of occupational safety and health (K3) on the part of Subak still does not pay much attention to this. By applying the K3 concept, the authors carry out an OHS analysis using the Hazard Identification Risk Assessment and Risk Control (HIRARC) method which is taking preventive measures to prevent and reduce the frequency of work accidents that occur there, and provide risk control recommendations to Subak. Hazard identification, risk assessment and risk control are part of the HIRARC method, after identifying the hazards of the 4 work processes in Subak there are 10 activities that have hazards and risks. The risk assessment shows 5 low categories, 3 medium categories, and 2 high risk categories, risk control in the form of giving a warning system, engineering control, administrative control, and the use of PPE, and at high risk redesigning the seed cleaner machine to reduce the potential danger from machine.